Upaya Peningkatan Kemampuan Aparat Desa dalam Pelaksanaan Tugas Administrasi Pemerintah di Desa - Basron Bachtiar (Jurnal Pemerintahan dan Politik, 2019)
ABSTRACTThe purpose of this study was to find out the efforts to increase the capacity of village officials in the implementation of government administrative duties in Terate Village and to find out the factors that influence efforts to increase the capacity of village officials in carrying out administrative tasks in Terate Village. In this study the data was collected by Interview, Observation and Study of Documents against the Head of Terate Village as a key informant (key informant), Secretary of the Terate Village and three heads of affairs. Analysis of the data in this study will be carried out in depth as an effort to find and organize systematically the results of observations, interviews and other information to improve the understanding of researchers about the case under study. The results of this study indicate that: efforts to increase the capacity of the Terate Village apparatus in carrying out the tasks of government administration, in particular the village administration which include: a. Employee discipline development b.) Education and training c.) Work motivation d.) Career development. Efforts to improve the capacity of the Terate Village apparatus are due to the conditions of carrying out village government duties due to several factors that surround village officials. The factors in question are the lack of skills / abilities of each village apparatus in connection with these tasks, the low level of work discipline in terms of time, the lack of guidance to the apparatus, supervision and ineffective control, and unfavorable working conditions.Keywords : Village Apparatus, Government AdministrationABSTRAKTujuan dari penelitian ini adalah untuk mengetahui upaya peningkatan kemampuan aparat desa dalam pelaksanaan tugas administrasi pemerintahan di Desa Terate dan untuk mengetahui faktor-faktor yang mempengaruhi upaya peningkatan kemampuan aparat Desa dalam pelaksanaan tugas administrasi pemerintahan di Desa Terate. Pada penelitian ini data dikumpulkan dengan Wawancara, Observasi dan Kaji Dokumen terhadap Kepala Desa Terate sebagai informan kunci (key informan), Sekretaris Desa Terate dan tiga orang kepala urusan. Analisis data dalam penelitian ini akan dilakukan secara mendalam sebagai upaya mencari dan menata secara sistematis catatan hasil observasi, wawancara dan informasi lainnya untuk meningkatkan pemahaman peneliti tentang kasus yang diteliti. Hasil penelitian ini menunjukan bahwa : upaya peningkatan kemampuan aparat Desa Terate dalam pelaksanaan tugas administrasi pemerintahan, khususrnya administrasi pemerintahan desa yang meliputi antara lain : a.) Pembinaan disiplin Pegawai  b.) Pendidikan dan pelatihan c.) Motivasi kerja d.) Pengembangan karir. Upaya peningkatan kemampuan aparat Desa Terate dikarenakan kondisi pelaksanaan tugas pemerintahan desa disebabkan oleh beberapa faktor yang melingkupi Aparat desa. Faktor-faktor yang dimaksud adalah minimnya keterampilan/kemampuan setiap Aparat desa sehubungan dengan tugas-tugas tersebut, masih rendahnya disiplin kerja ditinjau dari aspek waktu, minimnya pemberian bimbingan terhadap aparat, pengawasan dan, pengendalian yang tidak efektif, serta kondisi kerja yang kurang mendukung.Kata kunci : Aparat Desa, Administrasi Pemerintah